Insectivorous birds and environmental factors across an edge-interior gradient in tropical rainforest of Malaysia - Moradi, Hossein Varasteh; Zakaria, Mohamed; Mohd, Abdullah; Yusof, Ebil (2009)
The study objectives were to test: (1) the effects of the edge-interior gradient on under storey insectivorous bird abundance, density and diversity; (2) effects of environmental variables along an edge-interior gradient at population level (i.e., on each sub-guilds and species abundance); (3) possible effects of environmental structure along an edge-interior gradient at community level (i.e., species richness, diversity and total abundance). Fifteen hundred and four birds belonging to 49 species were recorded. Species composition differed along the edge-interior gradient at the guild and species level. The composition of insectivorous birds was correlated with the latter measured environmental variables. Based on bird-habitat associations along the edge-interior gradient, two groups were distinguished. Arboreal foliage gleaning insectivores were positively correlated with ground cover, light intensity, shrub cover and percent of shrub cover between 0.5 and 2 m high. While terrestrial insectivores, were sensitive to the forest edge and could indicate the quality of forest interior habitats associated with high humidity, dense canopy cover and deep litter depth. Forest remnants in the lowlands of Peninsular Malaysia that have a deep leaf litter layer, a dense canopy cover and high relative humidity are able to support insectivorous species that are sensitive to edge effects. As such these forests have important conservation value.